Epidemiology of renal and cardiovascular risk factors in toba aborigines - Bianchi, María Eugenia Victoria (2006)
Fil: Bianchi, María Eugenia Victoria. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.